Comparison of CHROMagar Salmonella Medium and Xylose-Lysine-Desoxycholate and Salmonella-Shigella Agars for Isolation of Salmonella Strains from Stool Samples - Maddocks, Susan (American Society for Microbiology, 2002)
The growth and appearance of 115 stock Salmonella isolates on a new formulation of CHROMagar Salmonella (CAS) medium were compared to those on xylose-lysine-desoxycholate agar (XLD), Salmonella-Shigella agar (SS), and Hektoen enteric agar (HEA) media. CAS medium was then compared prospectively to XLD and SS for the detection and presumptive identification of Salmonella strains in 500 consecutive clinical stool samples. All stock Salmonella isolates produced typical mauve colonies on CAS medium. Nine Salmonella strains were isolated from clinical specimens. The sensitivities for the detection of salmonellae after primary plating on CAS medium and the combination of XLD and SS after enrichment were 100%. The specificity for the detection of salmonellae after primary plating on CAS medium (83%) was significantly (P < 0.0001) higher than that after primary plating on the combination of SS and XLD media (55%) (a 28% difference in rates; 95% confidence interval, 23.0 to 34%). Twenty-nine non-Salmonella organisms produced mauve colonies on CAS medium, including 17 Candida spp. (59%) and 8 Pseudomonas spp. (28%). These were easily excluded as salmonellae by colony morphology, microscopic examination of a wet preparation, or oxidase testing. One biochemically inert Escherichia coli isolate required further identification to differentiate it from Salmonella spp. The use of plating on CAS medium demonstrated high levels of sensitivity and specificity and reduced the time to final identification of Salmonella spp., resulting in substantial cost savings. It can be recommended for use for the primary isolation of Salmonella spp. from stool specimens. Other media (e.g., XLD) are required to detect Shigella spp. concurrently.